2020
DOI: 10.1016/j.diagmicrobio.2020.115176
|View full text |Cite
|
Sign up to set email alerts
|

The use of copper to help prevent transmission of SARS-coronavirus and influenza viruses. A general review

Abstract: Objectives The SARS-CoV-2 is the causative agent of the COVID-19 disease a Severe Acute Respiratory Syndrome-Coronavirus (SARS-CoV). Its main transmission pathway is through large respiratory droplets, as well as direct and indirect contact. Copper in different format has been used in research and clinical settings to reduce the risk of bacterial and viral contamination. Therefore, this review aims to search for evidence about the biocidal properties of copper over coronaviridae family. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 31 publications
2
84
0
Order By: Relevance
“…Recently, Cortes and Zuñiga (2020) reviewed the scientific literature about the use of copper to prevent the potential transmission of influenza viruses and SARS-coronaviruses. According to these authors, the published data would support the use of this essential metal to inactivate viruses and a wide range of microorganisms.…”
Section: Essential Trace Elements and Covid-19mentioning
confidence: 99%
“…Recently, Cortes and Zuñiga (2020) reviewed the scientific literature about the use of copper to prevent the potential transmission of influenza viruses and SARS-coronaviruses. According to these authors, the published data would support the use of this essential metal to inactivate viruses and a wide range of microorganisms.…”
Section: Essential Trace Elements and Covid-19mentioning
confidence: 99%
“…The SARS-CoV-2 was inactivated by 99.9% in 1 h when exposed to Cu 2 O coated glass surfaces ( Behzadinasab et al, 2020 ), whereas 99.8% and 99.9% inactivation efficacy was observed for CuO coated solid surface in 30 min and 1 h exposure respectively ( Hosseini et al, 2021 ). A few reports have demonstrated Cu 2+ oxidative state in the form of CuS nanoparticles has demonstrated significant levels of antiviral properties against human Norovirus-like particles ( Broglie et al, 2015 ; Cortes and Zuñiga, 2020 ). However, potential attributions of Cu 2+ or S -2 were not elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the synergistic effect of inhibiting cytokine production and preventing destruction of T lymphocytes by increasing peripheral blood lymphocyte levels could also block overproduction of cytokines capable of suppressing an inflammatory reaction and the life-threatening pro-inflammatory cytokine storm (36). Additionally, as is known for copper and other chlorophyll a compounds, SCC may also act as an anti-viral agent (15). Therefore, maintaining homeostasis of the haematopoietic production of peripheral blood leukocytes, primarily of lymphocytes (46), may reduce the likelihood of disease progression to extreme severity.…”
Section: Sodium Copper Chlorophyllin and Covid-19mentioning
confidence: 99%
“…SSC exhibits significant anti-viral properties against a number of pathogenic viruses including the causative agents of highly infectious respiratory diseases such as influenza (14). A recent review suggested that in common with other copper-based compounds SCC could act as an anti-viral agent in the treatment of COVID-19 (15).…”
Section: Introductionmentioning
confidence: 99%